2016
DOI: 10.1007/s00122-016-2769-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus

Abstract: The Rsv1 - h gene in cultivar Suweon 97, which confers resistance to SMVs, was mapped to a 97.5-kb location (29,815,195-29,912,667 bp on chromosome 13) in the Rsv1 locus, thereby providing additional insights into the molecular nature underlying variations in resistance alleles in this particular locus. Soybean mosaic virus (SMV) is a well-known devastating pathogen of soybean (Glycine max (L.) Merrill.) causing significant yield losses and seed quality deterioration. A single dominant allele, Rsv1-h, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Recently, Ma et al . () mapped Rsv1‐h , which confers resistance to G1–G7, SC‐6N and SC‐7N strains, to a 97.5‐kb region and identified two CC‐NB‐LRR‐type R gene candidates in the Rsv1 chromosomal region. More detail on the Rsv1 chromosomal interval is provided in Table .…”
Section: Resistance Genes Of the Smv Pathosystemmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ma et al . () mapped Rsv1‐h , which confers resistance to G1–G7, SC‐6N and SC‐7N strains, to a 97.5‐kb region and identified two CC‐NB‐LRR‐type R gene candidates in the Rsv1 chromosomal region. More detail on the Rsv1 chromosomal interval is provided in Table .…”
Section: Resistance Genes Of the Smv Pathosystemmentioning
confidence: 99%
“…The Japanese system classifies SMV isolates into strains A, B, C, D and E, and considers both biological and sequence data (Saruta et al, 2005). The Chinese system uses several soybean differential lines to classify SMV strains SC1-21 (Li K. et al, 2010;Ma et al, 2016;Wang et al, 2003).…”
Section: Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rsc14-r was fine mapped in a 136.8-kb genomic region containing 16 candidate genes, but none of them belongs to NBS-LRR family (Table 5). However, Rsc14Q was positioned in the vicinity of Rsv1 on chromosome 13, the region which contains a cluster of NBS-LRR genes (Hayes et al 2004;Ma et al, 2011;Ma et al, 2016;Shi et al 2008;Yang et al, 2013) (Figure 3c). Moreover, linkage analysis revealed that the Rsc10-r was mapped on chromosome 6 (Figure 3b), while that of in KF (Rsc10) was located in the vicinity of Rsv4 on chromosome 2 (Li et al, 2012) (Figure 3d), of which resistance was probably attributed to an original class of disease resistance genes (Ilut et al 2016;Maroof et al, 2010;Zhao et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rsc14Q was positioned in the vicinity of Rsv1 on chromosome 13, the region which contains a cluster of NBS‐LRR genes (Hayes et al. ; Ma et al., ; Ma et al., ; Shi et al. ; Yang et al., ) (Figure c).…”
Section: Discussionmentioning
confidence: 99%